A contrastive analysis of Spanish and Chabacano concordance of forms and structures of noun-head modification - Macansantos, Armando B. 1917- ([Quezon City s.n.], 1971)
With the aim-in-view of helping Spanish teachers of Chabacano-speaking students in their preparation of teaching materials, this seminar paper aimed to describe and contrast Spanish and Chabacano structures of noun-head modification.
Thesis (M. Ed.)--University of the Philippines.
Typescript.
Keywords: Chabacano dialect -- Grammar, Comparative -- Spanish; Spanish language -- Grammar, Comparative -- Chabacano